Genotype by environment interaction for Holstein milk yield and fitness traits between Saudi Arabia and the United States - Al-Hur, Fahad Soliman, author; Bourdon, Richard M., advisor; Golden, Bruce, advisor; Brinks, James S., committee member; Iyer, Hariharan, committee member (Colorado State University. Libraries, 2002)
(Co)variance components and genetic parameters for Holstein first and all lactations mature equivalent milk and reproductive traits in the first four lactations were estimated by multiple-trait animal model using Method R procedures. The objectives of this study were to determine if genotype by environment interactions for milk yield and fitness traits exist between Saudi Arabia and the US and to investigate the relationship between milk yield and reproductive performance under a Saudi environment. The Saudi data included 46,777 records from 20,815 cows, daughters of 255 bulls and the US data included 38,293 records from 19,456 cows, daughters of 176 bulls. There were 151 sires common to both countries with average number of daughters 260 in the Saudi data and 246 in the US data. Herd-year-season was identified separately for first and multiple calving cows. Estimates of genetic correlations for milk yield between the two regions in first and all lactations were .68 and .17, respectively. In first lactation analysis, additive genetic variances were similar but residual variance was 21% smaller in Saudi Arabia than in the US. In the all-lactations analysis, additive genetic variance was 20% smaller for Saudi Arabia than for the US but residual variances were similar. Genetic correlations for gestation length and calving interval between the two countries were .96 and .99, respectively and the genetic correlation for age at first calving was low (0.10). The heritability estimate of the first lactation milk yield in Saudi Arabia (.29) was larger than the estimate in the US (.24) but the estimate from all lactations in the US (.34) was larger than the estimate in Saudi Arabia (.29). Phenotypic and environmental correlations between yield and fertility traits were positive (unfavorable). Genetic correlations between yield and days open, calving interval, number of services per conception, gestation length, and age at first calving were .44, .51, .19, -.05, and -.08, respectively. These results substantiate the presence of genotype by environment interaction for milk yield and age at first calving. Therefore, selection from within the Saudi Holstein population may be the best tool to identify the optimal animal for Saudi dairy production.
Keywords: anatomy and physiology; animals; animal diseases